Hepatectomy for Metabolic Associated Fatty Liver Disease (MAFLD) related HCC: Propensity case-matched analysis with viral- and alcohol-related HCC. Issue 1 (January 2022) - Conci, Simone; Cipriani, Federica; Donadon, Matteo; Marchitelli, Ivan; Ardito, Francesco; Famularo, Simone; Perri, Pasquale; Iaria, Maurizio; Ansaloni, Luca; Zanello, Matteo; La Barba, Giuliano; Patauner, Stefan; et al.
Abstract: Background and aims: We investigated the clinical impact of the newly defined metabolic-associated fatty liver disease (MAFLD) in patients undergoing hepatectomy for HCC (MAFLD-HCC) comparing the characteristics and outcomes of patients with MAFLD-HCC to viral- and alcoholic-related HCC (HCV-HCC, HBV-HCC, A-HCC). Methods: A retrospective analysis of patients included in the He.RC.O.Le.S. Group registry was performed. The characteristics, short- and long-term outcomes of 1315 patients included were compared according to the study group before and after an exact propensity score match (PSM). Results: Among the whole study population, 264 (20.1%) had MAFLD-HCC, 205 (15.6%) had HBV-HCC, 671 (51.0%) had HCV-HCC and 175 (13.3%) had A-HCC. MAFLD-HCC patients had higher BMI (p < 0.001), Charlson Comorbidities Index (p < 0.001), size of tumour (p < 0.001), and presence of cirrhosis (p < 0.001). After PSM, the 90-day mortality and severe morbidity rates were 5.9% and 7.1% in MAFLD-HCC, 2.3% and 7.1% in HBV-HCC, 3.5% and 11.7% in HCV-HCC, and 1.2% and 8.2% in A-HCC (p = 0.061 and p = 0.447, respectively). The 5-year OS and RFS rates were 54.4% and 37.1% in MAFLD-HCC, 64.9% and 32.2% in HBV-HCC, 53.4% and 24.7% in HCV-HCC and 62.0% and 37.8% in A-HCC (p = 0.345 and p = 0.389, respectively). Cirrhosis, multiple tumours, size and satellitosis seems to be the independent predictors of OS. Conclusion: Hepatectomy for MAFLD-HCC seems to have a higher but acceptable operative risk. However, long-term outcomes seems to be related to clinical and pathological factors rather than aetiological risk factors.